Strategi Pemanfaatan Microsoft Stream sebagai Layanan Audio Visual (AVA) di Perpustakaan ISI Padang Panjang - Sondra, Aivan (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
Technological developments that occur at this time have an influence on changes in services to libraries. The current audio-visual services are served on CD or DVD. So it is necessary to innovate in services in the form of digital services. The purpose of this study was to determine the use of Microsoft Stream as an audio-visual service at ISI Padang Panjang. The method used is qualitative with descriptive using observation, interview and literature techniques. The results of the study show that the use of Microsoft Stream is very useful, very easy, and has a good design so that users are very enthusiastic about using it.